The benefits of Tai Chi and brisk walking for cognitive function and fitness in older adults - Ji, Zhiguang (PeerJ, 2017)
The purpose of this study was to investigate the benefits of exercises with different cognitive demands for cognitive functions (Executive and non-Executive) in healthy older adults. A cross-sectional design was adopted. In total, 84 healthy older adults were enrolled in the study. They were categorized into the Tai Chi group (TG), the brisk walking group (BG) or the control group (CG). Each participant performed the Stroop task and a digit comparison task. The Stroop task included the following three conditions: a naming condition, an inhibition condition and an executive condition. There were two experimental conditions in the digit comparison task: the non-delay condition and the delay condition. The results indicated that participants of the TG and BG revealed significant better performance than the CG in the executive condition of cognitive tasks and fitness. There was no significant difference of reaction time (RT) and accuracy rate in the inhibition and delay conditions of cognitive tasks and fitness between the TG and BG. The TG showed shorter reaction time in the naming and the executive conditions, and more accurate in the inhibition conditions than the BG. These findings demonstrated that regular participation in brisk walking and Tai Chi have significant beneficial effects on executive function and fitness. However, due to the high cognitive demands of the exercise, Tai Chi benefit cognitive functions (Executive and non-Executive) in older adults more than brisk walking does. Further studies should research the underlying mechanisms at the behavioural and neuroelectric levels, providing more evidence to explain the effect of high-cognitive demands exercise on different processing levels of cognition.